A comparative study of fuzzy controlled genetic algorithms for reconfiguration of radial distribution systems - Prasad, , K; Sahoo, , NC (2005)
A lot of energy can be saved by efficient reconfiguration of radial distribution systems (RDS) under network constraints. In this paper, a novel genetic algorithm based approach has been adopted for network reconfiguration. The attractive features of the proposed approach are: an improved chromosome coding and an efficient convergence characteristics attributed to fuzzy controlled mutation. A systematic and comparative study of different genetic algorithms and simulation results has been presented and discussed.